Analysis of Inpatient Stroke Patient Characteristics at RSKD Dadi, South Sulawesi Province - Salsabila, Ainun; Yunus, Yusfina; Wahab, Bustaman (Physiotherapy, Exercise, and Rehabilitation Sciences Journal, 2026)
Aims: Stroke is a leading cause of death and disability worldwide. In South Sulawesi, the number of stroke cases has reached 21,490, ranking it as the sixth highest province in Indonesia. Methods: This study employed a quantitative approach with a cross-sectional design. Data collection was conducted using a total sampling technique with 165 patients, combining secondary data from medical records and primary data from family interviews. The study was conducted between January 15 and February 7, 2025. Results: The findings showed that ischemic stroke was the most common type (84.4%), predominantly affecting the elderly (57%). Females exhibited a higher prevalence (53.3%) than males (46.7%). The most common comorbidity was hypertension (67.9%), followed by dyslipidemia (55.2%) and diabetes mellitus (18.2%). Regarding lifestyle factors, 23.6% of the patients were smokers, and 4.2% reported alcohol consumption. There is no significant correlation between sex (p = 0.06), age (p = 0.77), comorbidities, including hypertension (p = 0.63), dyslipidemia (p = 0.09), and diabetes mellitus (p = 0.15) and lifestyle factors such as smoking (p = 0.95) and alcohol consumption (p = 0.96) with the type of stroke. Conclusion: Inpatients with stroke at RSKD Dadi were predominantly female, elderly, and diagnosed with ischemic stroke, and most commonly presented with hypertension as a comorbidity. Besides, there is no correlation between sex, age, comorbidities, and lifestyle factors with the type of stroke.